2015
DOI: 10.1016/j.sbspro.2015.03.434
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Cognitive Emotion Regulation between “B” Personality Disorders and Normal Persons

Abstract: The paper presents a Basical-Ex-Post facto research. 230 graduate students voluntarily answered the CERQ and MCMI III. The basic goal of this research is to compare four types of cluster B personality disorder who are identified by BR score of 60 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another study compared BPD and schizotypal PD, where the participants scored similarly on CERQ, except for the catastrophizing subscale that had higher scores in BPD patients [ 31 ]. Our study will have added value to the previous studies comparing BPD and HC groups by using CERQ [ 26 , 29 , 32 ], in as much as our research analyzes all the subscales of CERQ and determines effect sizes as well.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study compared BPD and schizotypal PD, where the participants scored similarly on CERQ, except for the catastrophizing subscale that had higher scores in BPD patients [ 31 ]. Our study will have added value to the previous studies comparing BPD and HC groups by using CERQ [ 26 , 29 , 32 ], in as much as our research analyzes all the subscales of CERQ and determines effect sizes as well.…”
Section: Introductionmentioning
confidence: 96%
“…This study suggests that dysfunctional cognitive emotion regulation can be a characteristic of personality disorders in general. Another study, however, shows no significant differences between people of cluster B personality disorders and healthy control in the nine cognitive emotion regulation strategies measured by CERQ [ 29 ]. Research found [ 30 ] that the use of maladaptive cognitive emotion regulation strategies (self-blame, blaming others, rumination, and catastrophizing) were related to high levels of negative affectivity and increased psychological problems in people with PDs.…”
Section: Introductionmentioning
confidence: 99%